Similar polyethylene wear between cemented and cementless Oxford medial UKA: a 5-year follow-up randomized controlled trial on 79 patients using radiostereometry - Horsager, Kristian; Madsen, Frank; Odgaard, Anders; Jepsen, Claus Fink; Rømer, Lone; Kristensen, Per Wagner; Kaptein, Bart L; Søballe, Kjeld; Stilling, Maiken (Acta Orthopaedica, 2018)
Background and purpose — Hydroxyapatite (HA)-coated implants have been associated with high polyethylene wear in hip arthroplasties. HA coating as a promoter of wear in knee arthroplasties has not been investigated. We compared the wear-rate of the polyethylene bearing for cemented and cementless HA-coated Oxford medial unicondylar knee arthroplasties (UKA). Secondarily, we investigated whether wear-rates were influenced by overhang or impingement of the bearing. Patients and methods — 80 patients (mean age 64 years), treatment-blinded, were randomized to 1 of 3 Oxford medial UKA versions: cemented with double-pegged or single-pegged femoral component or cementless HA-coated with double-pegged femoral component (ratios 1:1:1). We compared wear between the cemented (n = 55) and cementless group (n = 25) (ratio 2:1). Wear, impingement, and overhang were quantified between surgery and 5-year follow-up using radiostereometry. Clinical outcome was evaluated with the Oxford Knee Score. Results — The mean wear-rate for patients without bearing overhang was 0.04 mm/year (95% CI 0.02–0.07) for the cemented group and 0.05 mm/year (CI 0.02–0.08) for the cementless group. The mean difference in wear was 0.008 mm/year (CI –0.04 to 0.03). No impingement was identified. Half of the patients had medial bearing overhang, mean 2.5 mm (1–5). Wear increased by 0.014 mm/year for each mm increment in overhang. The mean Oxford Knee Score was 39 for the cementless group and 38 for the cemented group at the 5-year follow-up. Interpretation — The wear-rates were similar for the 2 fixation methods, which supports further use of the cementless Oxford medial UKA. However, a caveat is a relatively large 95% CI of the mean difference in wear-rate. Component size and position is important as half of the patients presented with an additional increase in wear-rate due to medial bearing overhang.